2011
DOI: 10.1039/c1ce05650f
|View full text |Cite
|
Sign up to set email alerts
|

A carbamazepine-indomethacin (1 : 1) cocrystal produced by milling

Abstract: An X-ray amorphous mixture of carbamazepine and indomethacin transforms upon annealing to produce a novel 1:1 cocrystal, whose structure has been determined from laboratory powder X-ray diffraction (PXRD) data. Carbamazepine (CBZ; Fig 1) crystallises in five known 65 method, CBZ:IND is detectable by PXRD after ca. 48hrs storage at 25°C and the characteristic CBZ:IND peaks continue to grow in intensity and sharpen with time as crystallization proceeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The core hydrogen bonding motifs are essentially the same in both the previously reported CBZ:IND form I [24] and CBZ:IND form II, taking the general form illustrated in Figure 3b, i.e., a central R 2 2 (8) synthon and an N-H•••O hydrogen bond between the amide of the CBZ and the oxygen of the 4-chlorobenzoyl group of the IND. The density of form II (1.398 g cm −3 ) is higher than that of form I (1.351 g cm −3 ), which is indicative of more efficient packing in form II.…”
Section: Atom Cbz:ind Form II Indmet03supporting
confidence: 72%
See 1 more Smart Citation
“…The core hydrogen bonding motifs are essentially the same in both the previously reported CBZ:IND form I [24] and CBZ:IND form II, taking the general form illustrated in Figure 3b, i.e., a central R 2 2 (8) synthon and an N-H•••O hydrogen bond between the amide of the CBZ and the oxygen of the 4-chlorobenzoyl group of the IND. The density of form II (1.398 g cm −3 ) is higher than that of form I (1.351 g cm −3 ), which is indicative of more efficient packing in form II.…”
Section: Atom Cbz:ind Form II Indmet03supporting
confidence: 72%
“…Cl 1 0.118 Å 0.058 Å C 9 0.234 Å 0.119 Å Taken together, these geometry changes affect the location of a significant amount of X-ray scattering power, explaining why the initial rigid-body Rietveld refinement based on the starting INDMET03 geometry was unsuccessful. The core hydrogen bonding motifs are essentially the same in both the previously reported CBZ:IND form I [24] and CBZ:IND form II, taking the general form illustrated in Figure 3b, i.e., a central (8) synthon and an N-H⋅⋅⋅O hydrogen bond between the amide of the CBZ and the oxygen of the 4-chlorobenzoyl group of the IND. The density of form II (1.398 g cm −3 ) is higher than that of form I (1.351 g cm −3 ), which is indicative of more efficient packing in form II.…”
Section: Atom Cbz:ind Form II Indmet03supporting
confidence: 71%
“…Majumder et al reported [83] a carbamazepine-indomethacin cocrystal using the powder X-ray diffraction (PXRD) structure solution. PXRD data shows a clear formation of cocrystal during ball mill grinding.…”
Section: Carbamazepine Cocrystal Systemmentioning
confidence: 99%
“…These results, where reduced supersaturation is observed, are in contradiction with the current paradigm of formulating drugs together as an amorphous mixture or producing them as cocrystals for the purpose of improved dissolution and increased supersaturation. [7,[13][14][15]34] Therefore, the maximum achievable supersaturation for various ATV:RTV molar ratios was investigated in order to better understand this phenomenon.…”
Section: Atv and Rtv Miscibilitymentioning
confidence: 99%